EVALUATION OF ACUTE AND SUBCHRONIC TOXICITY OF TIEU TICH GIANG PHI-HV HARD CAPSULE EXTRACT IN EXPERIMENTAL ANIMALS (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the safety of Tieu tich giang phi-HV hard capsules through acute and subchronic oral toxicity studies in experimental animals.Method: Acute oral toxicity was assessed in Swiss albino mice using the Litchfield-Wilcoxon method. Subchronic oral toxicity was evaluated in Wistar rats administered the test product continuously for 28 days in accordance with the guidelines of the World Health Organization and the Vietnamese Ministry of Health.Results: In the acute toxicity study, Tieu tich giang phi-HV hard capsules administered at the highest tested dose, equivalent to 20.83 times the proposed human dose (45 capsules/kg, corresponding to 18.45gr of extract/kg), caused no mortality or signs of acute toxicity in mice; therefore, the LD₅₀ could not be determined. In the subchronic toxicity study, rats receiving the test product at doses of 442.8 mg/kg/day and 1328.4 mg/kg/day showed no abnormal changes in general condition, hematological parameters, biochemical indices, or gross and histopathological features of the liver and kidneys. No statistically significant differences were observed between the treated groups and the control group (p > 0.05).Conclusion: Tieu tich giang phi-HV hard capsules did not produce acute toxicity and were demonstrated to be safe at the tested doses during the 28-day subchronic oral toxicity assessment in experimental animals
Keywords: Tieu tich giang phi-HV, hard capsules, acute toxicity, subchronic toxicity, experimental study.